2021
DOI: 10.1016/s2214-109x(20)30481-2
|View full text |Cite
|
Sign up to set email alerts
|

A scorecard of progress towards measles elimination in 15 west African countries, 2001–19: a retrospective, multicountry analysis of national immunisation coverage and surveillance data

Abstract: Summary Background The WHO Regional Office for the Africa Regional Immunization Technical Advisory Group, in 2011, adopted the measles control and elimination goals for all countries of the African region to achieve in 2015 and 2020 respectively. Our aim was to track the current status of progress towards measles control and elimination milestones across 15 west African countries between 2001 and 2019. Methods We did a retrospective multicountry series anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 18 publications
4
25
1
Order By: Relevance
“…When Masresha et al (2018) included The Gambia in their 2012–2016 assessment of the elimination status of measles in 11 African countries with high routine MCV1 coverage [ 17 ], they concluded that none of the countries assessed were ready for the verification of their measles elimination status [ 17 ]. Wariri et al (2021) developed a scorecard which they used to track the progress of 15 West African (ECOWAS) countries towards measles control and elimination milestones between 2001 and 2019 [ 24 ]. They found that although 3 countries including The Gambia have made substantial achievements to measles, the ECOWAS block is not track to achieving measles elimination in 2020 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When Masresha et al (2018) included The Gambia in their 2012–2016 assessment of the elimination status of measles in 11 African countries with high routine MCV1 coverage [ 17 ], they concluded that none of the countries assessed were ready for the verification of their measles elimination status [ 17 ]. Wariri et al (2021) developed a scorecard which they used to track the progress of 15 West African (ECOWAS) countries towards measles control and elimination milestones between 2001 and 2019 [ 24 ]. They found that although 3 countries including The Gambia have made substantial achievements to measles, the ECOWAS block is not track to achieving measles elimination in 2020 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wariri et al (2021) developed a scorecard which they used to track the progress of 15 West African (ECOWAS) countries towards measles control and elimination milestones between 2001 and 2019 [ 24 ]. They found that although 3 countries including The Gambia have made substantial achievements to measles, the ECOWAS block is not track to achieving measles elimination in 2020 [ 24 ]. Since their aim was to mainly assess progress towards measles elimination, Masresha et al (2018) and Wariri et al (2021) did not include further analysis such as the epidemiology of cases, risk factors, and vaccine effectiveness, which would also be useful in informing measles control and elimination strategies at country level [ 17 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the mortality rate from several measles outbreaks, measles remains one of the most vaccine-preventable diseases, which has also yielded tremendous results over the years in Africa—an improvement in vaccination coverage has led to decreased incidence from 145 to 120 cases per million populations between 2000 and 2019 [ 1 , 3 ]. Although the target set by the World Health Assembly to eradicate measles by 2020 was not achieved [ 1 , 3 ]. This is partly due to non-immunization or partial immunization of children in the poor/underserved communities, malnutrition, vaccine hesitancy, poor surveillance, and weak health care systems in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) had recommended a 95% vaccination for herd immunity against measles. However, according to a retrospective multi-country series analysis of national immunization coverage and case surveillance data in 15 West African countries carried out by Wariri et al, the measles-containing vaccine first dose (MCV1) coverage range from 45% in 2001 to 66% in 2019 and only 7 out of 15 countries has introduced a second dose of measles-containing vaccine (MCV2), since 2015 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%